Non-Observance Politeness Maxim and Implicature on the TV Show Kids Say The Darndest Things - Salsabila, Talitha (English Literature Study Program, 2023)
The phenomenon of language development in the modern era is increasingly rapid through mass media, one of which is television shows. In addition to providing information, television also provides audiovisual entertainment to attract people to enjoy it. The non-observance maxim of politeness committed by public figures can be found. In this study, the author wants to examine how the non-observance politeness maxim and its implicature is in the video TV Show